Defesa da poesia ou a paixão do poeta (o caráter soteriológico da poesia na concepção hilstiana) - Silva, Nívia Maria Santos (2009)
This dissertation has the objective of analyzing poet Hilda Hilst’s conception about the poetic doing and about the one who performs it within the context of contemporaneity from literary compositions, interviews, testimonies, general notes, showing the coherence that she presented among her ideas, her life and her work. In the corpus of this dissertation, texts of her poetic work are analyzed, specially Júbilo, Memória, Noviciado da Paixão, more specifically the part entitled Poems to men of our time, there are also poems and excerpts in prose of several books. From them, it is worked that soteriological character that Hilst attributed to literature and to its agents. For such thing, it is retaken the existing idea in the Classical Antiquity of the poet as the guardian of the memory and holder of knowledge. Besides, through the hilstian text analysis, it is attempted to demonstrate how the priorities of the contemporary society contrast with the priorities of the poetic doing, which leads the poet to be seen as secondary and dispensable. Through this analysis, it is worked how Hilda Hilst reacts to this situation defending the poet and the poetry that, regardless the social economic political context, in her view, it will always be indispensable to recuperate the soul, the beauty and the freedom of the man.